PENGARUH TOXIC LEADERSHIP DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI SURABAYA DENGAN KOMUNIKASI SEBAGAI VARIABEL INTERVENING - Nuradi Mulya Razaq; Siti Mujanah; Achmad Yanu Alif Fianto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to analyze the influence of toxic leadership and work stress on employee performance in Surabaya with communication as an interverning variable. In various companies there are still toxic leaders who make employees uncomfortable which can cause employee performance to be less than optimal, and work stress caused by the work environment and excessive workload can affect employee performance, therefore good communication is maintained. In this research, samples were taken using an online questionnaire which was distributed to 100 employee respondents in Surabaya so that the data used a 1-5 Likert scale and this analysis was processed using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS). ) method. So the results of this research show that communication has a positive effect on employee performance, toxic leadership has a significant effect on communication variables, toxic leadership has a positive effect on employee performance, work stress has a negative and insignificant effect on communication and employee performance. , toxic leadership has a significant positive effect on performance. employee. employees through communication as an intervening variable. The research results show that the level of toxic leaders among employees in Surabaya can be minimized by providing communication between employees and superiors so that it can increase employee comfort in carrying out employee performance. This communication has a positive impact on employee performance at the Surabaya Company.